SUPPORT SYSTEM LEMBAGA KEUANGAN SYARIAH DALAM PENGEMBANGAN UMKM HALAL KOTA MEDAN - Abdul Hadi Ismail; Khairunnisa Khairunnisa; Riyan Pradesyah; Al Bara (Jurnal Akuntansi dan Pajak, 2023)
This study aims to see the support system carried out by Islamic financial institutions to halal MSMEs in the city of Medan. So far, many financial institutions have provided financing to MSMEs without any guidance to entrepreneurs to carry out business development. Where financial institutions only give money and customers are obliged to return, but when entrepreneurs want to develop their products, banks or financial institutions are unable to provide education related to the development that entrepreneurs will make. This research is a descriptive qualitative research, where the researcher conducts an interview with the object that is cooled, then narrates it and draws conclusions from the results of the interview conducted. From the results of the research obtained, that Islamic banks or Islamic financial institutions, some provide training on business development, some are just providing financing. The financing used in this study used the murabahah bil wakalah contract